PENGARUH KECANDUAN INTERNET, DAYA TARIK PROMOSI DAN KEPEMILIKAN KARTU KREDIT TERHADAP PERILAKU PEMBELIAN IMPULSIF ONLINE - Putra, A.A. Ngr Bagus Maha; Kusuma, A.A.G. Agung Artha (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
The purpose of this study is ntuk determine the effect of internet addiction, attraction and promotion of credit card ownership to the online impulsive buying behavior. This study used quantitative research by using surveys and questionnaires to 105 respondents. It was found that Internet addiction is significantly positive influence on impulsive buying behavior online in Indonesia. The appeal of the promotion also has a positive and significant influence on online purchasing behavior implsif in Indonesia. Lastly, credit card ownership is significantly positive influence on online behavior in Indonesia the purchase impulsive.
Keywords: Kecanduan Internet; Daya Tarik Promosi; Kepemilikan Kartu Kredit; Pembelian Impulsif Online